Capacity Building Kader Posyandu untuk Deteksi Dini dan Monitoring Penyakit Hipertensi dan Dibetes Melitus: Capacity Building for Cadres of Integrated Service Post for Early Detection and Monitoring of Hypertension and Diabetes Mellitus - Puspitasari, Nunik; Sulistyorini, Yuly; Mahmudah, Mahmudah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
In Indonesia, 70 out of 100 people with non-communicable diseases do not realize they have a non-communicable disease. The estimated number of people with hypertension aged > 15 years in 2021 in Ngawi Regency is 271,604 people, while the number of people with diabetes who receive health services is 33,715 people. The purpose of this Community Service activity is to increase the knowledge and skills of cadres so that they can carry out early detection and monitoring of hypertension and diabetes mellitus. Community service activities were carried out at the Walikukun Community Health Centre, Ngawi Regency, East Java Province with 80 participants. The method of implementation of the first activity is exposure and discussion of hypertension and diabetes guided by the Head of Puskesmas Walikukun, and the second is the practice of measuring blood pressure and blood sugar levels using digital measuring instruments. The results of the community service showed that cadres who improved their knowledge about diabetes were 63.9%. Cadres who improved their knowledge of hypertension were 62.3%. Cadres who improved their practical skills in measuring blood pressure were 27.9%, while cadres who improved their skills in measuring blood sugar levels with a digital glucometer were 19.7%. Cadres need to get knowledge and skills periodically about early detection of non-communicable diseases so that they can provide education and conduct early detection in the community.